2020
DOI: 10.1016/j.jcot.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Acetabulum fractures in elderly: A systematic review of fracture pattern and treatment

Abstract: Acetabulum fractures are being increasingly seen with low impact injuries in elderly patients. This article aimed to study systematically literature on geriatric acetabulum fractures. Objectives of this systematic review were to study (1) demography of patients, common mechanisms of injury and types of fracture patterns commonly seen in elderly patients, (2) treatment used for these fractures in literature and (3) mortality rates in elderly with these fractures. Methods: Systematic search was carried out in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
1
15
0
3
Order By: Relevance
“…When displaced, they usually require operative intervention to maintain joint stability and prevent the development of post-traumatic arthritis. 8 The management of these anterior column fractures should ideally be undertaken by an appropriately qualified orthopaedic trauma surgeon and requires the advanced resources of a trauma center. Treatment of such patients with severe acetabular fractures at a level 1 trauma center has been shown to result in decreased mortality rate and improved physical function at one year compared to those treated at level II trauma or non-trauma centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When displaced, they usually require operative intervention to maintain joint stability and prevent the development of post-traumatic arthritis. 8 The management of these anterior column fractures should ideally be undertaken by an appropriately qualified orthopaedic trauma surgeon and requires the advanced resources of a trauma center. Treatment of such patients with severe acetabular fractures at a level 1 trauma center has been shown to result in decreased mortality rate and improved physical function at one year compared to those treated at level II trauma or non-trauma centers.…”
Section: Discussionmentioning
confidence: 99%
“…7 Acetabular fractures involving the anterior column are one of the most common types of acetabular fractures sustained by the elderly and the high superior pubic ramus fracturedalso known as the pubic root fracturedcan be misread as anterior column fracture by the radiologists. 8 This can result in unnecessary health care costs because a patient with a stable pubic root fracture who may be safely managed at a community hospital may be transferred to a Level 1 trauma center due to a radiology report incorrectly identifying the fracture as an "anterior column fracture". 9,10 Thus, correctly distinguishing the stable pelvic ring injury, from an anterior column fracture may not only reduce health care costs but also provide a more accurate prognosis for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…This type of fixation is most suited for patients who have nondisplaced or minimally displaced fractures that are at risk for displacement, or those who cannot walk because of pain. Studies have shown that the benefits of CRPF include decreased blood loss, shorter operative time, shorter length of stay, and fewer medical complications compared with patients who undergo ORIF 51 . Despite these benefits, there are limitations to a percutaneous approach.…”
Section: Orthopaedic Surgerymentioning
confidence: 99%
“…In addition, preexisting osteoarthritis of the hip is often observed in older patients. Recent literature specified the most common fracture patterns with both column fractures (19%), followed by anterior column and posterior hemi-transverse fractures (17%) and anterior column fractures (17%) according to the Letournel classification [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%